2017
DOI: 10.33588/fem.201.874
|View full text |Cite
|
Sign up to set email alerts
|

El examen MIR 2015 desde el punto de vista de la teoría de respuesta al ítem

Abstract: El examen MIR lo convocan anualmente, desde 1978, los Ministerios de Sanidad y Educación, y se realiza en el mismo día y hora en toda España. La convocatoria se publica en el Boletín Ofi cial del Es-tado unos meses antes de su realización. En los últimos años, la convocatoria se ha publicado en el mes de septiembre y los exámenes se han celebrado a finales de enero o principios de febrero del año inmediatamente posterior. En el caso de la convocatoria de 2015, ésta se realizó por medio de la Orden

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The use of an overall mean to compare above or below this mark is helpful to reflect the performance of five-different groups of test-takers that revealed us which specialties had the students with the best scores. The ENARM global mean for the minimum score (from 2012 to 2019) was 72.572 a score above the previous observation made in a study by de la Garza-Aguilar 6 ; this number is also above the mean for the past 7 years for the test known as MIR (Medical Intern Resident) in Spain with 57.29 reported by the Ministry of Health 21,22 . Our findings showed that the surgical specialties whose applicants achieve scores above this mean were ophthalmology, otorhinolaryngology, and general surgery.…”
Section: Grouping Of Specialties Above or Below A Global Meanmentioning
confidence: 42%
“…The use of an overall mean to compare above or below this mark is helpful to reflect the performance of five-different groups of test-takers that revealed us which specialties had the students with the best scores. The ENARM global mean for the minimum score (from 2012 to 2019) was 72.572 a score above the previous observation made in a study by de la Garza-Aguilar 6 ; this number is also above the mean for the past 7 years for the test known as MIR (Medical Intern Resident) in Spain with 57.29 reported by the Ministry of Health 21,22 . Our findings showed that the surgical specialties whose applicants achieve scores above this mean were ophthalmology, otorhinolaryngology, and general surgery.…”
Section: Grouping Of Specialties Above or Below A Global Meanmentioning
confidence: 42%
“…The use of an overall mean to compare above or below this mark is helpful to reflect the performance of five-different groups of test-takers that revealed us which specialties had the students with the best scores. The ENARM global mean for the minimum score (from 2012 to 2019) was 72.572 a score above the previous observation made in a study by de la Garza-Aguilar 6 ; this number is also above the mean for the past 7 years for the test known as MIR (Medical Intern Resident) in Spain with 57.29 reported by the Ministry of Health 21,22 . Our findings showed that the surgical specialties whose applicants achieve scores above this mean were ophthalmology, otorhinolaryngology, and general surgery.…”
Section: Grouping Of Specialties Above or Below A Global Meanmentioning
confidence: 42%
“…The use of an overall mean to compare above or below this mark is helpful to reflect the performance of eight different groups of test-takers that revealed to us which specialities had the students with the best scores. The ENARM global mean for the minimum score (from 2012 to 2019) was 69.133, a score above the previous observation made in a study by de la Garza-Aguilar [4]; this number is also above the mean for the last seven years for the test known as MIR (Medical Intern Resident) in Spain with 57.29 reported by the Ministry of Health [28,29]. Our findings showed that the clinical specialities whose applicants achieved scores above this mean were Internal medicine, Anesthesiology, Pediatrics, and Pneumology.…”
Section: Grouping Of Specialities Above or Below A Global Meanmentioning
confidence: 45%